2011
DOI: 10.1016/j.jtcvs.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of intracardiac leiomyomatosis

Abstract: Surgical treatment of intracardiac leiomyomatosis can result in satisfactory midterm to long-term survival and satisfactory heart function. Multiple surgical strategies should be tailored to the anatomic characteristics of the intracardiac leiomyoma. Recurrence of intracardiac leiomyomatosis after the resection procedure may result in unfavorable late result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 20 publications
(21 reference statements)
0
36
0
Order By: Relevance
“…Most cardiac leiomyomas described in the literature are extensions of an intravenous leiomyomatosis [2], and we have found only one previous report of a primary cardiac leiomyoma [5]. The latter was diagnosed in an asymptomatic 13-year-old boy and described as an intracardiac mass located in the lateral free wall of the right ventricle [5].…”
Section: Discussionmentioning
confidence: 84%
“…Most cardiac leiomyomas described in the literature are extensions of an intravenous leiomyomatosis [2], and we have found only one previous report of a primary cardiac leiomyoma [5]. The latter was diagnosed in an asymptomatic 13-year-old boy and described as an intracardiac mass located in the lateral free wall of the right ventricle [5].…”
Section: Discussionmentioning
confidence: 84%
“…Currently, no more than 10 cases of right intracardiac tumor have been completely resected through abdominal incision [11,12]. ey believed that the resection of the tumor through abdominal incision should meet the following requirements: (1) the tumor was free in the inferior vena cava and right atrium; (2) the maximum diameter of the tumor was smaller than the minimum diameter of the inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the tumor had no adhesion to the inferior vena cava; however, it adhered tightly to the right internal iliac vein. After undergoing these two surgeries and reviewing the literature [9][10][11][12], we found that most of the tumors were free in the inferior vena cava and the right atrium. It was assumed that the tumors in the right atrium could be removed directly through abdominal incision, avoiding thoracotomy to establish extracorporeal circulation.…”
Section: Operative Procedurementioning
confidence: 99%
“…Resections of the intracardiac and intravenous tumors through atriotomy and venotomy in a one-stage or twostage manner are the common strategies for surgical treatment of ICL 1,2 ; however, patients have to undergo double incisions (ie, thoracotomy and laparotomy). Unlike other intra-IVC tumors, such as the friable renal tumor, ICL is characteristically of high tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical strategies have already been established according to the morphology of the ICL. 1,2 This case study introduces a strategy of single-stage resection through a laparotomy under peripheral cardiopulmonary bypass (CPB).…”
mentioning
confidence: 99%